Motivação dos colaboradores e sua influência na gestão de pessoas em pequenas empresas de serviços na cidade de São Paulo - Oliveira, Everton Ferreira de (2011)
This dissertation had as object of investigation the motivation of the collaborators and their influence in people management, delimitated to the scene of small services companies in São Paulo city. The analysis units were the companies Ambienty and Z500. The phenomenological method was used, the qualitative research approach, the strategy of multicase study and the interview techniques, observation and analysis of documents for data lift. The theoretical foundation has taken as base the theories developed by classic authors, into the purposed theme, as Maslow (1943), Herzberg (1959) and McGregor (1960). The research subjects were collaborators, Human Resources managers and owners of these companies. For data treatment the content analysis and the documental analysis were used. As research question it was discussed how the motivation of collaborators influences the people management in small service companies. The theme of motivation coupled with people management was used for identification of motivation factors and the hygienic factors existent in those cases. The results point the difficulties of owners, managers and collaborators in comprehend and reinforce the variables implied in these classic theories to arouse / maintain their intrinsic motivation at work. Nevertheless, trust in proximity relationship to obtain organizational results is a result that presents evidence of the desire of maintaining among hierarchic levels, in both companies, the naturalness and humanities behind each person. The research question was answered as motivation exerting reciprocal influence, without any hierarchic level preponderating over the other regarding to motivational factors. Regarding to hygienic factors it was evidenced, in both companies, that the care and attention with those factors stimulate the retention of collaborators.